Rectifying Attenuated Store-Operated Calcium Entry as a Therapeutic Approach for Alzheimer’s Disease - Huang, Alexis S.; Tong, Benjamin C.K.; Wu, Aston J.; Chen, Xiaotong; Sreenivasmurthy, Sravan G.; Zhu, Zhou; Liu, Jia; Su, Chengfu; Li, Min; Cheung, King-Ho (Current Alzheimer Research, 2020)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder. Although the pathological hallmarks of AD have been identified, the derived therapies cannot effectively slow down or stop disease progression; hence, it is likely that other pathogenic mechanisms are involved in AD pathogenesis. Intracellular calcium (Ca2+) dyshomeostasis has been consistently observed in AD patients and numerous AD models and may emerge prior to the development of amyloid plaques and neurofibrillary tangles. Thus, intracellular Ca2+ disruptions are believed to play an important role in AD development and could serve as promising therapeutic intervention targets. One of the disrupted intracellular Ca2+ signaling pathways manifested in AD is attenuated storeoperated Ca2+ entry (SOCE). SOCE is an extracellular Ca2+ entry mechanism mainly triggered by intracellular Ca2+ store depletion. Maintaining normal SOCE function not only provides a means for the cell to replenish ER Ca2+ stores but also serves as a cellular signal that maintains normal neuronal functions, including excitability, neurogenesis, neurotransmission, synaptic plasticity, and gene expression. However, normal SOCE function is diminished in AD, resulting in disrupted neuronal spine stability and synaptic plasticity and the promotion of amyloidogenesis. Mounting evidence suggests that rectifying diminished SOCE in neurons may intervene with the progression of AD. In this review, the mechanisms of SOCE disruption and the associated pathogenic impacts on AD will be discussed. We will also highlight the potential therapeutic targets or approaches that may help ameliorate SOCE deficits for AD treatment.
Keywords: store-operated calcium entry